Doing it Twice: Asymmetric Deprotonation/Alkylation of Weiss Diketone Derivatives as Key Steps in the Functionalization of Bicyclo[3.3.0]octanes1. Issue 4 (10th December 2012) - Lutz, Vanessa; Park, Natja; Rothe, Christian; Krüger, Claudia; Baro, Angelika; Laschat, Sabine
Abstract: The silyl‐protected allylhydropentalenone derivative9, derived from the Weiss diketone, was functionalized by enantioselective deprotonation in the presence of lithium bis(1‐phenylethyl)amide/LiCl as the chiral base, which was generated in situ from bis(1‐phenylethyl)ammonium chloride [( R, R )‐ or ( S, S )‐14 ] and BuLi, and trapping of the resulting enolate with alkyl halide electrophiles to give pseudo‐ C 2 or ‐ Cs ‐symmetrical bicyclo[3.3.0]octanones10 and11 . The influence of the chiral base and electrophiles on the regioselectivity and double stereodifferentiation was investigated. Taking the double stereocontrol into account, a matched selectivity for the pseudo‐ C 2 pair (1 R, 4 R )‐10 /(1 S, 4 R )‐10 and a mismatched selectivity for the pseudo‐ Cs pair (1 S, 6 R )‐11 /(1 R, 6 R )‐11 were observed in the presence of ( R, R )‐14 . The use of ( S, S )‐14, however, produced a mismatched selectivity for (1 R, 4 R )‐10 /(1 S, 4 R )‐10 and a matched selectivity for (1 S, 6 R )‐11 /(1 R, 6 R )‐11 with complementary diastereoselectivity depending on the electrophile. Furthermore, the hydropentalenone derivative10a provided an alternative route to the bicyclo[3.3.0]octene core of the macrocyclic tetramic acid lactam, cylindramide (5 ). Abstract : Pseudo‐ C 2 ‐symmetrical bicyclo[3.3.0]octanones2 have been prepared from enantiopure α‐substituted derivatives1 of the Weiss diketone. The symmetrical bicyclo[3.3.0]octanones2 were then converted into the hydropentalene core of macrocyclic polyketide tetramic acid lactams such as cylindramide.